Protozoan parasites of Musca domestica Linnaeus (DIPTERA: MUSCIDAE) from Lima. Two new records in Peru - Cárdenas, Martín (2001)
The goal of this research was to increase the knowledge of two parasitic protozoa: Herpetomonas muscarum (Leidy, 1856) Ken, 1880 and Octosporea muscaedomesticae Flu, 1911, in Musca domestica. Both represent new records in Peru. The H. muscarum leptomonad are 36 µ long and are larger than the ones cited by other authors. O. muscadomesticae presents large and plasmodial forms slightly larger than the ones studied by Bulnheim & Vávra (1998). In the M. domestica group surveyed, we determined a significant percentage of H. muscarum (54,0%) and O. muscadomesticae (27,0%).